VD_FINDINFO Décision / 2015 / 671 vom 30. Juni 2015 - VD Tribunal cantonal (2015)
NON-LIEU, DÉCISION D'IRRECEVABILITÉ, LÉSÉ, PLAIGNANT, DIFFAMATION, CALOMNIE | 173 CP, 174 CP, 30 al. 1 CP, 310 CPP (CH), 319 CPP (CH)